2011
DOI: 10.1158/1940-6207.capr-11-0137
|View full text |Cite
|
Sign up to set email alerts
|

Oral Azathioprine Leads to Higher Incorporation of 6-Thioguanine in DNA of Skin than Liver: The Protective Role of the Keap1/Nrf2/ARE Pathway

Abstract: Azathioprine is a widely used anti-inflammatory, immunosuppressive, and anticancer agent. However, chronic treatment with this drug is associated with a profoundly increased risk (in certain cases by more than 100-fold) of developing squamous cell carcinoma of the skin. Incorporation of its ultimate metabolite, thio-dGTP, in DNA results in partial substitution of guanine with 6-thioguanine which, combined with exposure to UVA radiation, creates a source of synergistic mutagenic damage to DNA. We now report tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 45 publications
1
20
1
Order By: Relevance
“…As expected, the 6-TG levels in skin DNA were much higher than the corresponding levels in liver (Fig. 3), consistent with our previous observations (36). Compared with control animals, the levels of 6-TG in DNA isolated from ventral skin of TBE-31-treated animals were reduced by 30% (P ¼ 0.023).…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…As expected, the 6-TG levels in skin DNA were much higher than the corresponding levels in liver (Fig. 3), consistent with our previous observations (36). Compared with control animals, the levels of 6-TG in DNA isolated from ventral skin of TBE-31-treated animals were reduced by 30% (P ¼ 0.023).…”
Section: Resultssupporting
confidence: 91%
“…28,34,35). We have observed a very similar level of 6-TG incorporation in skin DNA isolated from SKH-1 hairless mice that had been treated orally with azathioprine (36). In the same study, we also found that genetic upregulation of the Keap1/Nrf2/ARE pathway (by Keap1-knockdown) reduces the 6-TG DNA levels in murine skin and liver by approximately 30%.…”
Section: Introductionmentioning
confidence: 54%
See 3 more Smart Citations